1998
DOI: 10.1016/s0006-3495(98)77726-4
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Dipole Effects on Channel Permeation. I. Experiments with (5F-Indole)Trp13 Gramicidin A Channels

Abstract: Gramicidin A (gA), with four Trp residues per monomer, has an increased conductance compared to its Phe replacement analogs. When the dipole moment of the Trp13 side chain is increased by fluorination at indole position 5 (FgA), the conductance is expected to increase further. gA and FgA conductances to Na+, K+, and H+ were measured in planar diphytanoylphosphatidylcholine (DPhPC) or glycerylmonoolein (GMO) bilayers. In DPhPC bilayers, Na+ and K+ conductances increased upon fluorination, whereas in GMO they de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
135
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(169 citation statements)
references
References 69 publications
34
135
0
Order By: Relevance
“…1C); in the (misfolded) DS structures (Fig. 1D), the outer Trp 13 and Trp 15 (colored magenta in Fig. 1) retain positions close to the bilayer/solution interface, whereas the inner Trp 9 and Trp 11 (colored maroon in Fig.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1C); in the (misfolded) DS structures (Fig. 1D), the outer Trp 13 and Trp 15 (colored magenta in Fig. 1) retain positions close to the bilayer/solution interface, whereas the inner Trp 9 and Trp 11 (colored maroon in Fig.…”
mentioning
confidence: 99%
“…Previous experiments on gA 3 suggested that the indole dipole moment (13)(14)(15)(16)(17) has a direct influence on membrane protein function (ion permeation) and that indole NH hydrogen bonding is important for the conformational preference of gA (18,19). More generally, indole N-H hydrogen bonding appears to be important for protein folding and dynamics (20).…”
mentioning
confidence: 99%
See 3 more Smart Citations